Jumping Plant-lice of Slovenia (Insecta: Hemiptera: Psylloidea) - Seljak, Gabrijel (Scopolia, 2020)
A complete faunistic overview of psyllids recorded in Slovenia is presented. Altogether, 129 species are listed: Aphalaridae - 18, Calophyidae - 1, Homotomidae - 1, Liviidae - 12, Psyllidae - 50, and Triozide - 47 species. Eighteen species recorded in Slovenia are listed here for the first time. Historical records for the species Cacopsylla parvipennis, Bactericera perrisii and T. viridula could not have been confirmed recently, hence their occurrence in Slovenia is doubtful. Previously published records of Trioza kiefferi as the causal agent of galls on leaves of Rhamnusalpinus subsp. fallax are shown here to be erroneous and concern the eriophyid mite Calepitrimerus rhamni. Provided herewith are distribution maps for all species, colour photographs of various developmental stages for most species as well as of their host plants.
Keywords: boljšice; Hemiptera; Insecta; insects; psyllids; Psylloidea; Slovenia; Slovenija; zoologija; zoology; žuželke